CMC and the Connection Between Virtual Utopias and Actual Realities - Richards, Cameron (Javnost-The Public, 1999)
People are often ambivalent about the potential future roles of new technologies (and the Internet specifically) and their possible effects on human society. There has been a tendency for polarisation between attitudes or perceptions of naive enthusiasm and cynical resistance towards the use of computers and digital networks, and for such related concepts as "the information superhighway," "cyberspace" and "virtual communities." The projection of such ambivalent perceptions into naively utopian (or even ironically dystopian) images and narratives might be seen as the latest and uniquely global permutation of a basic function of human culture -- that is, to imagine "a better future" or represent "an ideal past." This paper considers the extent to which the kinds of virtual utopias made possible by computer-mediated communication are "connected" to the actual individual and social realities of human participants. In other words, should a distinction be made between the use of virtual utopias (and utopian representations in any culture) as merely escapist, self-indulgent fantasy on the one hand, and as a useful, transformative media for reinventing the human condition on the other?